Seasonal movements of wisents (Bison bonasus L., 1758) in the Bieszczady Mountains (SE Poland) - Perzanowski, Kajetan; Januszczak, Maciej; Wołoszyn-Gałęza, Aleksandra (Biological Letters, 2013)
We studied seasonal movements of wisents (also known as European bison) from the western subpopulation in the Bieszczady Mountains, in forest districts of Baligród, Komańcza, Lesko, and Cisna. The estimation of distance of seasonal movements was based on telemetric bearings of 4 adult animals (1 cow and 3 bulls) in 2002‑2005. We assumed that a maximum distance of movement was a linear extent between 2 most distant locations of an animal recorded in winter and in the following growing season. The maximum distances were 12.8‑18.5 km for the cow, and 5.1‑22.9 km for bulls. Wisent movements were triggered by significant changes in ambient temperature (decrease in late autumn and increase in early spring) and the appearance of first snowfall in autumn.